2016
DOI: 10.1186/s13148-016-0218-1
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profiling identifies novel markers of progression in hepatitis B-related chronic liver disease

Abstract: BackgroundChronic hepatitis B infection is characterized by hepatic immune and inflammatory response with considerable variation in the rates of progression to cirrhosis. Genetic variants and environmental cues influence predisposition to the development of chronic liver disease; however, it remains unknown if aberrant DNA methylation is associated with fibrosis progression in chronic hepatitis B.ResultsTo identify epigenetic marks associated with inflammatory and fibrotic processes of the hepatitis B-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Genes involved in immunity and inflammation are logical candidates for the convergent epigenetic effects of IDU. DNA methylation (DNA-me), one of the major epigenetic mechanisms, generally suppresses, while demethylation generally increases, gene transcription, and both play important roles in inflammatory processes associated with cardiovascular disease, cancer, and infectious disease 12 18 . We recently reported that the methylation of genes in immune and inflammation domains in white blood cells (WBC) differed significantly between HIV-infected and uninfected individuals 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Genes involved in immunity and inflammation are logical candidates for the convergent epigenetic effects of IDU. DNA methylation (DNA-me), one of the major epigenetic mechanisms, generally suppresses, while demethylation generally increases, gene transcription, and both play important roles in inflammatory processes associated with cardiovascular disease, cancer, and infectious disease 12 18 . We recently reported that the methylation of genes in immune and inflammation domains in white blood cells (WBC) differed significantly between HIV-infected and uninfected individuals 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Both genome-wide hypomethylation and region-specific hypermethylation are present not only in HCC but also in preneoplastic conditions [ 51 , 52 , 53 ]. Moreover, CpG methylation signatures have been associated with the progression of HVB-related liver disease [ 54 ], NAFLD fibrosis [ 55 , 56 ] and cirrhosis [ 57 ], and the poor survival of HCC patients [ 58 ]. DNA methylation changes repressing hepatic HNF4A-dependent gene expression have been associated with the loss of hepatocellular functions observed in patients with alcoholic hepatitis [ 59 ].…”
Section: Epigenetic Reprogramming In Liver Disease: Changes In Epimentioning
confidence: 99%
“…Recently, through hepatic genome-wide methylation profiling, hypermethylation of HOXA2 and HDAC4 along with hypomethylation of PPP1R18 were identified and significantly linked to severe fibrosis in patients with CHB. cytosine-guanine dinucleotide methylation within HOXA2, PPP1R18 and HDAC4 genes might serve as genetic markers for progression of CHB [ 81 ].…”
Section: Host Genetic Markersmentioning
confidence: 99%